1999
DOI: 10.1111/j.1600-065x.1999.tb01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against helminth parasites ‐ the ultimate challenge for vaccinologists?

Abstract: Helminths are multicellular pathogens which infect vast numbers of human and animal hosts, causing widespread chronic disease and morbidity. Vaccination against these parasites requires more than identification of effective target antigens, because without understanding the immunology of the host-parasite relationship, ineffective immune mechanisms may be invoked, and there is a danger of amplifying immunopathogenic responses. The fundamental features of the immune response to helminths are therefore summarise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 224 publications
(16 reference statements)
0
52
0
Order By: Relevance
“…There are few effective vaccines against helminth pathogens (25), and while chemotherapy is often curative, it provides no protection from reinfection. One of the remarkable features of the Mf stage of B. malayi is its longevity, which is likely to be many months in the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…There are few effective vaccines against helminth pathogens (25), and while chemotherapy is often curative, it provides no protection from reinfection. One of the remarkable features of the Mf stage of B. malayi is its longevity, which is likely to be many months in the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been put forward to explain the underlying mechanisms of T-cell down-regulation in filariasis (20). In studies of lymphatic filariasis, IL-10 has been shown to regulate T-cell responses in both animal models and clinical studies (23,25).…”
Section: Discussionmentioning
confidence: 99%
“…A predominant feature of parasitic nematodes is their uniform ability to induce type 2 immune responses in their hosts, a feature that they share with other parasitic helminths (14,33). However, despite the extensive characterization of the immune responses to helminth infections, the antigens and mechanisms responsible for driving the distinct Th2 subset bias are still unknown.…”
mentioning
confidence: 99%